Stock Price Determination: Empirical Evidence from ROA, BOPO, LDR, and Firm Size In Digital Bank of Indonesia (2020-2024) - Anka Fandini; Andre Suryaningprang; Riyandi Nur Sumawidjaya; Yoyo Sudaryo (eCo-Fin, 2026)
This study examines the effects of ROA, BOPO, LDR and Firm Size on Stock Price of Indonesian Digital Bank between 2020 and 2024. Employing a quantitative approach that adopts a descriptive and verificative approach, the study looks at 30 financial statements from specific Indonesian Digital Bank industry. The correlations between the variables were evaluated using analysis of multiple linear regression, the coefficient of determination test, traditional assumption tests, as well as the product moment correlation coefficient test such as t-tests and F-tests for assessing hypotheses. The data was processed utilizing SPSS 21.0. According to the test findings that are not complete, all of the variables do not impacted to Stock Price. Including, the simultaneous test findings show that ROA, BOPO, LDR and Firm Size do not have a major influence when combined on Stock Price. According to these results, activity ROA, BOPO, LDR and Firm Size mix are not more important factors in determining Stock Price in the Indonesian Digital Bank industry than short-term, this may result from the procedures employed or a lack of data.